Studi Pengaruh Waktu Fermentasi terhadap Kualitas Nutrisi Tepache Berbahan Dasar Kulit Nanas (Ananas comosus (L.) Merr) - Ahmad Fahri Muzzaqi; Ambar Rukmini; Eman Darmawan; Dyah Titin Laswati (Universitas Widya Mataram, 2026)
This study aimed to evaluate the effect of different fermentation durations on the chemical, microbiological, and organoleptic qualities of tepache made from pineapple peel (Ananas comosus L. Merr) and to determine the optimal fermentation time. The fermentation process was carried out spontaneously at room temperature (±28–30°C) for 24, 48, 72, and 96 hours. The parameters observed included total sugar content, pH, vitamin C, flavonoid levels, total lactic acid bacteria (BAL), and organoleptic attributes such as taste, aroma, color, and overall preference. Laboratory chemical analyses, total plate count (TPC) methods for BAL, and hedonic sensory tests with untrained panelists were employed. The results demonstrated that fermentation time significantly affected all observed parameters. Longer fermentation times led to a decrease in total sugar and flavonoids, while pH and vitamin C levels increased. BAL counts peaked at 24 hours and declined thereafter. The 24-hour fermentation treatment produced the best results across chemical, microbiological, and sensory parameters, with a total sugar content of 1.36%, pH 3.66, vitamin C 5.94 mg/100 mL, flavonoid content 0.0038 mg/mL, and BAL count of 6.1×10⁷ CFU/mL. These findings suggest that pineapple peel has promising potential as a raw material for the development of functional beverages.